1995
DOI: 10.1038/bjc.1995.325
|View full text |Cite
|
Sign up to set email alerts
|

Growth arrest vs direct cytotoxicity and the importance of molecular structure for the in vitro anti-tumour activity of ether lipids

Abstract: Summary A panel of 25 different lipid agents was evaluated for in vitro activity against HT29 human colon carcinoma and HL60 promyelocytic leukaemia cells by 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay. The structure-activity relationships seen with this series, including those for four sets of positional or stereoisomers, indicate that specific receptor proteins are unlikely as targets for anti-tumour lipid (ATL) action. Additional data confirm the lack of involvement of the plate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 61 publications
3
15
0
Order By: Relevance
“…There is evidence that inhibition of cell growth caused by ET-18-OCH 3 at sublytic concentrations (below 5±10 lM) results from cell-cycle arrest and apoptosis [4,10,11,21,22,25]. Flow cytometry analysis of dierent cell sub-populations indicated that a subpopulation that had characteristics of apoptotic cells (smaller size/higher cell density; forward compared to side scattering on¯ow cytometry plots) had low levels of CD11b and CD71 expression, suggesting that up-regulation of these markers is not directly associated with cell death.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is evidence that inhibition of cell growth caused by ET-18-OCH 3 at sublytic concentrations (below 5±10 lM) results from cell-cycle arrest and apoptosis [4,10,11,21,22,25]. Flow cytometry analysis of dierent cell sub-populations indicated that a subpopulation that had characteristics of apoptotic cells (smaller size/higher cell density; forward compared to side scattering on¯ow cytometry plots) had low levels of CD11b and CD71 expression, suggesting that up-regulation of these markers is not directly associated with cell death.…”
Section: Discussionmentioning
confidence: 99%
“…We have shown previously that ET-18-OCH 3 and ELL-12 induce DNA fragmentation, as a marker of apoptosis, in L1210 cells [25] and in U-937 cells (data not shown), indicating the inhibition of cell growth is at least partly due to apoptosis. However, it has also been shown that incubation of cells with ET-18-OCH 3 can result in cell-cycle arrest [4,11,21]. Thus, growth inhibition by ET-18-OCH 3 may result from more than one mechanism.…”
Section: Growth-inhibitory Eects Of Et-18-ochmentioning
confidence: 99%
“…In addition to the apoptotic effect, ET-18-OCH 3 has been reported to inhibit cell division without concurrent inhibition of nuclear division, leading to accumulation of cells in G 2 /M, multinucleate cell formation, and subsequent cell death through apoptosis [124][125][126][127][128][129][130][131] (Mollinedo, F., del Canto-Jañez, E., Verhaegen, S. and Gajate, C., unpublished data). Inhibition of cell growth by ET-18-OCH 3 resulted from inhibition of cytokinesis [131,132] (Mollinedo, F., del Canto-Jañez, E., Verhaegen, S. and Gajate, C., unpublished data) by an unknown mechanism.…”
Section: Effects Of Et-18-och 3 On Cell Cycle and Mitosismentioning
confidence: 99%
“…In particular, this principle for targeted drug delivery is independent of the size of the diseased region and does not require a preceding localization of the diseased tissue. Furthermore, by designing the carrier liposome to include special lipids whose degradation products, after exposure to sPLA 2 , are converted into permeability enhancers, enzymatic activators, or certain drugs such as anticancer lysoetherlipids [55], a possible realization of Dr Erlich's 'magic bullet' can be imagined. …”
Section: Resultsmentioning
confidence: 99%